Implementing language learning strategies for writing descriptive text in an open area at a senior high school - Julianty Julianty; Andi Asrifan; Prodhan Mahbub Ibna Seraj; Amitabh Vikram Dwivedi; Muhammad Mujtaba Asad (International Journal of Humanities and Innovation (IJHI), 2022)
This research aims to determine the effectiveness of language learning strategies in writing descriptive text in an open area. Also, this research is subject to investigate the significant difference in students’ achievement before and after implementing learning strategies in writing using descriptive text in an open area. The researchers applied pre-experimental research with one group pre-test and post-test design and collected the data by giving a pre-test, treatment, and post-test. The research sample was a public senior high school in Tana Toraja regency, South Sulawesi, Indonesia, consisting of thirty students. The research findings showed that the tenth-grade senior high school students had fair to poor scores in a pre-test. After giving treatment, their writing skill in descriptive text significantly increased. The research results showed that implementing language learning strategies in writing descriptive text in an open area is effective. Also, the investigation showed a significant difference in students' achievement before and after being taught using language learning strategies in writing descriptive text in an open area. However, the teacher's responsibility as an instructor is to ensure students understand the topic in writing, particularly when creating descriptive language. To help students comprehend writing better, the teacher should provide some basic writing instruction. Writing descriptive language in an open space helps students learn writing more quickly and easily. To measure their significance for English language education innovation, open area learning methodologies should be investigated further to enhance other abilities like reading or speaking.